2015
DOI: 10.7740/kjcs.2015.60.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The Ratooning Potential of Several Early-Ripening Rice Cultivar in Korea

Abstract: Rice ratooning is the production of a second rice crop from the stubble left behind after the main-crop harvest. The main advantage of rice ratooning is that in areas where rice is the main crop, double crop of rice can be grown for additional returns. Eight cultivars of rice were tested for estimation their ratooning ability. The main crop was harvested at mass maturity, after which the tillers were mowed to stubbles of about 10 cm tall. And then left without any further input, until the ratooned plant were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Although we detected a high correlation in some varieties ('M 488' and 'M 225') for temperature parameters (T max and T mean ), the minimum temperature was the only factor that correlated significantly to the TF in the average of all varieties. This result confirms the consequence of Shin et al who reported a higher significant impact (0.759 *) on TF [14]. On the other hand, the grain threshability depends on the shape of the separation pilei [20], the strength of spikelet attachment to the panicle [30], and the different moisture contents of the seed [31].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although we detected a high correlation in some varieties ('M 488' and 'M 225') for temperature parameters (T max and T mean ), the minimum temperature was the only factor that correlated significantly to the TF in the average of all varieties. This result confirms the consequence of Shin et al who reported a higher significant impact (0.759 *) on TF [14]. On the other hand, the grain threshability depends on the shape of the separation pilei [20], the strength of spikelet attachment to the panicle [30], and the different moisture contents of the seed [31].…”
Section: Discussionsupporting
confidence: 86%
“…More research groups reported that the grain threshing habit of rice is related to three factors: the form of the abscission layer (AL) at the base of sterile lemmas [12,13], environmental factors such as humidity and temperature [8,14], and the genetic constitution of the variety [15][16][17]. Although the formation of the AL is determined by genes [12,18], a classification based on the AL is very difficult [19].…”
Section: Introductionmentioning
confidence: 99%